The use of Laissez-faire style by teachers of Learning Disabilities in English language according to some variables - Mohamad Ahmad Saleem Khasawneh (Newinera Publisher, 2021)
This study aimed at identifying the use of laissez-faire style in classroom management by teachers of learning disabilities in English language in the light of some variables. The study population consisted of all (60) teachers in the upper basic stage in Irbid Governorate. The study sample consisted of (30) male and female teachers. The study used the descriptive approach and developed a questionnaire as an instrument to collect data. The results of the study showed that there were statistically significant differences for the use of laissez-faire style due to the gender variable based on the calculated (t) value of (4.14), and the differences were in favor of males, as evidenced by their high mean score. The mean score for the responses of males teachers was (2.14), and for female teachers (1,83).